ANALISIS DAMPAK DESENTRALISASI FISKAL TERHADAP ANGKA MELEK HURUF PEREMPUAN DAN ANGKA PARTISIPASI SEKOLAH PEREMPUAN DI KABUPATEN/KOTA PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Galih Pramilu Bakti; Johanna Maria Kodoatie (Universitas Diponegoro, 2012)
ABSTRACT Fiscal decentralization has been adopted worldwide. The common motive of many countries adopted fiscal decentralization because it potentially improve performance of the public sector. Since the “UU No. 22/ 1999” and “UU No 25/1999” released and revised by “UU No 32/2004” and “UU No 33/2004” it have impact local government in Indonesia, because they have role to decide local government finance. It also assumted that local government improving public services for women. That measured by women access to education sector. This paper use panel data which analyze with Fixed Effect Methods model. Data series on local goverments of Daerah Istimewa Yogyakarta is contructed for the years 2004-2009. The variabel is local revenue, government expenditure, population, per capita income, amount of highschool. Finding suggest that fiscal decentralization which analyze with Fixed Effect Methods Model does not have significant influence to women education access in Daerah Istimewa Yogyakarta.